Some results on the integral transforms - Dernek, Ayse Nese; Aylikci, Fatih (Tubitak Scientific & Technological Research Council Turkey, 2017)
In this paper, the authors consider the P-v,P-2n-transform, the g(n)-transform, and the kappa(v,n)-transform as generalizations of the Widder potential transform, the Glasser transform, and the kappa(v)-transform, respectively. Many identities involving these transforms are given. A number of new Parseval Goldstein type identities are obtained for these and many other well-known integral transforms. Some useful corollaries for evaluating infinite integrals of special functions are presented. Illustrative examples are given for the results.
Keywords: Laplace transforms; L-2n-transforms; Widder potential transforms; Glasser transforms; Hankel transforms; kappa(v) transforms; P-v,P-2n-transforms; g(n)-transforms; Parseval-Goldstein type theorems; Mathematics